INVESTIGATION OF BIOGENIC SILVER NANOPARTICLES GREEN SYNTHESIZED FROM CARICA PAPAYA - Konjari, Reshma S.; Jacob, Anju A.; Jayanthi, S.; Ramalingam, C.; Ethiraj, Anita S. (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: This work mainly focuses on the investigation of optical, structural and morphological characteristics of Silver nanoparticles (Ag-NPs) synthesized using Papaya (Carica Papaya) leaf extract and to study the mechanisms involved in the formation. Methods: Ag-NPs were synthesized using colloidal method from silver nitrate using aqueous leaf extract of Papaya as reducing agent. Spectral analysis of Ag-NPs was done using UV-Vis spectroscopy and optical characteristics were studied. Fourier Transform Infrared (FTIR) analysis was done to investigate the mechanisms involved in the reaction. A detailed study of structural and morphological properties was done using X-Ray Diffraction (XRD) and Atomic Force Microscopy (AFM). Results: Spherical shaped Ag-NPs of Face Centered Cubic (FCC) structure were formed and the average particle size was in the range 25-35 nm. Conclusion: Papaya is a good reducing agent for the synthesis of Ag-NPs. Since it is a plant with medicinal values, thus synthesized Ag-NPs can be used for medicinal implications. Â